ANALISIS IKAN HASIL TANGKAPAN NELAYAN DI TEMPAT PENDARATAN IKAN (TPI) PANTERAJA PIDIE JAYA - Ukhwatul Khamisah; Faisal Syahputra; Agus Naufal; Elfa Yeni (JURNAL KREASI RAKYAT, 2025)
Panteraja District is a coastal area in Pidie Jaya Regency. Most of the residents work as fishermen. Fish catch plays an important role as a source of income for the local community. The activity of unloading fish catches at the Panteraja Fish Landing Place (TPI) is quite busy, catch data is needed in fishing activities as a basis for planning, development and decision-making or fisheries policies. This study aims to determine the composition of the dominant fish and analyze the length and weight of fish caught at the Panteraja TPI, Pidie Jaya Regency. This study uses a quantitative descriptive method. The data used are primary data obtained through direct observation and interviews, as well as secondary data obtained from reference sources related to the research. Fish sampling used a simple random sampling system. The number of fish samples is 3 samples per boat that docked at the Panteraja TPI coast. Fish length measurements used a 30 cm ruler, while for measuring the total weight of the fish, the tool used was a digital scale with an accuracy of 0.1 grams. Based on observations and analysis of the catch composition from February to March 2025, the study showed that the fish catch at the Panteraja Fish Farm consisted of 5 families and 7 species with a total weight of 13,278 kg. The percentage value was obtained by comparing the weight per species with the total weight of all species caught at the Panteraja Fish Farm. The species with the highest weight (kg) is the petek fish (Leiognathus brevirostris) with a composition of 5,130 kg or 38.64% of the total catch and the species with the lowest composition is the ribbon fish (Trichiurus lepturus) at 121 kg or 0.91% of the total catch. The relationship between the length and weight of fish caught at TPI Panteraja obtained positive allometric conditions (b>3) and negative (b<3). Skipjack tuna is positively allometric with a b value = 4.0931, while the petek fish, pelaling fish, anchovies, dencis fish, mackerel and ribbon fish are negatively allometric with a b value <3. The relationship between the length and weight of fish is influenced by several factors, such as: differences in species, variations in fish size, sex, gonad development, food availability, parasites, and diseases as well as physiological factors, the environment, sampling procedures and fishing gear used.